Comparisons of thermodynamic and economic performances of cryogenic air separation plants designed for external and internal compression of oxygen. (September 2019) - Singla, Rohit; Chowdhury, Kanchan
Highlights: Four cryogenic air separation units producing pressurized oxygen are modelled. Attaching a crude argon column reduces specific power consumption. Internal compression (IC) plant consumes more power than an external compression one. Pressure and flow of air in main heat exchanger optimized for IC plants. Abstract: Cryogenic air separation plants producing pressurized gaseous oxygen (PGOX) near 40 bara at purities 99.8% and 95% and gaseous nitrogen at 5 bara above 99.99% purity are analyzed. Oxygen is compressed either by external compression process (EC) or by internal compression (IC). IC is gasification of pumped liquid oxygen in the main heat exchanger (MHX). IC plants require appropriate combinations of pressure and flow of air and size of the MHX to vaporize PGOX with reasonable specific power consumption (SPC). Based on exergy and economic analyses of the ASU after simulating the plant in Aspen HYSYS®™8.6, the values of parameters which give high exergy efficiency with low capital and operating expenditures are determined. SPC of IC is 7–8% higher than that of EC. Addition of crude argon column improves the purity of oxygen from 96.3% to 99.8%. Recovery of oxygen improves by 5% with 3–4% reduction of SPC for both types of plants. Capital requirement for both EC and IC plants is about 50% higher with argon separation than without it. HP air between 33% and 31% of total air flow at 70 bara and 80 bara respectively is the most preferred range of operation of IC plants for 95% purity of oxygen. The corresponding flow of HP air is 5% lower for 99.8% purity of oxygen.